Monoclonal antibodies for chronic migraine and medication overuse headache: A real-world study - Krymchantowski, Abouch V.; Jevoux, Carla; Krymchantowski, Ana Gabriela; Silva-Néto, Raimundo Pereira (Frontiers in Neurology, 2023)
Background Medication-overuse headache is highly prevalent in tertiary care centers. It may be a cause or consequence of the overuse of symptomatic medications for migraine attacks. Objective We aimed to compare the efficacy of anti-CGRP monoclonal antibodies (mAbs) added to conventional pharmacological treatments in patients with chronic migraine (CM) and medication overuse headache (MOH). Methods A cross-sectional, prospective, randomized, open study with real-world comparison groups of patients was carried out. The sample consisted of 200 patients with CM and MOH, who received the same approach to withdraw overused medications, started preventative treatment, and either did or did not receive mAbs. Results A total of 172 patients (126 women and 46 men) were included in the study and divided into two groups: group one consisting of 58 patients (control) and group two of 114 patients who used mAbs added to conventional pharmacological agents. The mean age was 44.1 ± 13.6 years, ranging from 18 to 78 years. In the 3 months follow-up after starting the treatment, both groups presented headache frequency reduction, but those with monoclonal antibodies had a significantly higher reduction in the number of headache days and symptomatic medication intake when compared to the control (p < 0.0001). Conclusions The addition of an anti-CGRP monoclonal antibody to the treatment for medication overuse headaches in chronic migraineurs may result in decreasing headache frequency and symptomatic medication use when compared to conventional treatments with drugs.